Evaluation of the tissue distribution, excretion, and cytochrome P450 induction studies of a potential antitumor agent, TM-2, in animals using LC-MS/MS. (2nd September 2017) - Men, Lei; Zhao, Yunli; Lin, Hongxin; Tang, Xing; Yu, Zhiguo
Abstract: 1. TM-2 is a promising novel semi-synthetic taxane derivative with greater antitumor activity especially against resistant tumors and lower toxicity compared with docetaxel. Information on distribution and excretion of the pharmaceutical in animals, as well as biochemical information relevant to potential drug interactions should normally be evaluated prior to human clinical trials. 2. The present study investigated the tissue distribution and excretion of TM-2 in animals following intravenous administration for further advancement of the molecule. The potential inductive effect of TM-2 on cytochrome P450 iso-enzymes CYP 3A1 in rats was also evaluated. 3. The tissue distribution study in mice showed that TM-2 was rapidly dispersed in the various tissues and peak concentration levels were achieved within 0.083–1 h. The highest concentration was detected in pancreas, followed by lung, kidney, spleen, heart and liver. TM-2 was mainly excreted in the feces via the bile (0.14% of the dose) and urinary excretion was minimal (0.007%). TM-2 increased CYP3A1 enzyme activities with time and dose dependence in rat liver microsome. 4. This important data serve as a useful resource to support further research of TM-2 and allow intelligent assessment of toxicology and in vivo activity testing performed in animals.